Pregnancy outcomes in patients with chronic myeloid leukemia treated with imatinib mesylate: short report from a developing country. Issue 9 (September 2014) - Iqbal, Javaid; Ali, Zafar; Khan, Aruj-un-Nisa; Aziz, Zeba
Abstract Treatment of chronic myeloid leukemia (CML) is challenging in patients who want to conceive. We followed 809 patients with CML treated with imatinib mesylate (IM). We observed outcomes in 90 pregnancies from 61 patients (21 females, 40 males) who conceived while on IM. Information was obtained on duration of exposure to IM, pregnancy termination and congenital abnormalities. Hematologic and cytogenetic responses were also recorded. Twenty-eight pregnancies occurred among females, while 62 were reported from male patients. Among female patients, 19 (67.9%) pregnancies were uneventful while six (21.4%) ended in adverse events. Only 12 (57%) females reported their pregnancies. Three (4.4%) adverse events were reported from male patients. Pregnancy is an important part of life in our young patients due to cultural and societal pressures. It is paramount to counsel pregnant patients to switch to drugs with no adverse effect on the developing fetus. However, lack of communication is a major factor preventing physicians from counseling patients about conception.